Transepidermal water loss rises before food anaphylaxis and predicts food challenge outcomes - Schuler, Charles F.; O’Shea, Kelly M.; Troost, Jonathan P.; Kaul, Bridgette; Launius, Christopher M.; Cannon, Jayme; Manthei, David M.; Freigeh, George E.; Sanders, Georgiana M.; Hogan, Simon P.; Lukacs, Nicholas W.; Baker, James R. (The Journal of clinical investigation, 2023)
Food allergy (FA) is a growing health problem requiring physiologic confirmation via the oral food challenge (OFC). Many OFCs result in clinical anaphylaxis, causing discomfort and risk while limiting OFC utility. Transepidermal water loss (TEWL) measurement provides a potential solution to detect food anaphylaxis in real time prior to clinical symptoms. We evaluated whether TEWL changes during an OFC could predict anaphylaxis onset. Physicians and nurses blind to TEWL results conducted and adjudicated the results of all 209 OFCs in this study. A study coordinator measured TEWL throughout the OFC and had no input on OFC conduct. TEWL was measured two ways in two separate groups. First, TEWL was measured using static, discrete measurements. Second, TEWL was measured using continuous monitoring. Participants who consented gave blood before and after OFCs for biomarker analyses. TEWL rose significantly (2.93 g/m2/h) during reactions and did not rise during non-reacting OFCs (-1.00 g/m2/h). Systemic increases in tryptase and interleukin-3 were also detected during reactions, providing supporting biochemical evidence of anaphylaxis. The TEWL rise occurred 48 minutes earlier than clinically evident anaphylaxis. Continuous monitoring detected a significant rise in TEWL that presaged positive OFCs, but no rise was seen in OFCs with no reaction, providing high predictive specificity (96%) for anaphylaxis against non-reactions 38 minutes prior to anaphylaxis. During OFCs, a TEWL rise anticipates a positive clinical challenge. TEWL presents a novel monitoring modality that may predict food anaphylaxis and facilitate improvements in OFC safety and tolerability.